Robbe-Grillet's métaphoricité fantôme - Thomas D. O'Donnell (Studies in 20th & 21st Century Literature, 1977)
Alain Robbe-Grillet made his initial reputation among French writers not only through his controversial first novels, but also through a number of essays published collectively under the title of Pour un Nouveau Roman. In these essays, Robbe-Grillet pronounced an absolute condemnation of metaphor in the novel; this condemnation has since been prominently featured in theoretical arguments focusing on "zero-degree" writing. However, Robbe-Grillet has since written fictions which are hardly consistent with his earlier doctrine, and Topologie d'une cité fantôme appears, if anything, to embrace metaphor, and thus to point to a new direction in Robbe-Grillet's work, a direction closer to that of Simon and Ricardou.
Keywords: Alain Robbe-Grillet; nouveau roman; new novel; Topologie d' une cité fantôme